Investigating illegal drug use by socially integrated and well-resourced young adults in Cape Town - Reuter, Joshua (Department of Public Law, 2022)
There is a dearth of data or literature regarding frequent non-dependent drug use by well resourced, socially integrated South Africans. South African literature regarding drug use – which has primarily focused on dependent drug use accompanied by socio-economic or health crises – is thus incomplete. The purpose of this dissertation was primarily to investigate how well-resourced young adults in Cape Town, South Africa legitimise their illegal drug use habits – and the accompanying potential moral condemnation by society – within otherwise socially conforming lives. The first leg of the data collection process was an anonymous, self-administered survey, in which 84 young, well-resourced professionals or postgraduate students participated. The second leg of data collection involved semi-structured interviews with ten voluntary participants. A thematic approach was adopted in analysing the data. Three themes were identified. In the first – the ‘social life' framework – drug use was posited as playing an important role in enhancing social gatherings or larger social events, and thus being socially accommodated and normalised in certain social contexts. Narratives falling within the ‘relaxation' framework accounted primarily for habitual cannabis use, which was described as a valid way to unwind after a long day – much like alcohol. In both the first and second frameworks, control and responsibility were emphasised to justify drug use, thus drawing on a neo-liberal conception of the self as autonomous and self-controlled. Finally, the ‘psychedelic adventure' framework accounted for certain participants' infrequent and location-specific use of hallucinogenics. Although acknowledged to result in a loss of control, this form of drug use was seen as an escape from the rigours of daily life, in order to rejoin reality revitalised, and not as a departure from accepted social priorities. The findings of this study align with many modern theories of drug use; most notably normalisation. They further support a policy shift, from punishing drug use as a pathology, to a focus on harm reduction. However, more data and more multifaceted analyses are certainly required.